UTILIZATION OF APPLICATION PROGRAM IN SUPPORTING ASSESSMENT OF ENGLISH PERFORMANCE - Adityo Adityo; Agista Nidya Wardani (Schemata: Jurnal Pascasarjana UIN Mataram, 2019)
English has been taught in early years of school and become one of the main course in the school based on the need of global society while not every school is able to offer the course due to the lack of qualified teachers. The evaluation needed in the learning process face a difficulty in which due to the lack of qualified teachers, is only capable of doing test and not evaluation. Based on the phenomena, this research is conducted to find a new method of evaluating English course by using language tools software that can be used by non-English teacher in accurate and valid evaluation and projected to modernised evaluation process in English course and able to support distance learning. The research employs quantitative analysis in a series of four data collections and analyses involving four participants over the time of 3 months. This research is further supported by language analysis from language expert as a secondary instrument to validate the result of the analysis from the main instrument, P_LEX language tools. The result of the research shows that language tools is valid as a supporting device for evaluating language performance as the result of the language analysis is in parallel to the analysis of language expert.